Charles BETTELHEIM, Cultural Revolution and Industrial Organization in China Changes in management and the división of labor. New York, Monthly Review Press, 1974, 128 pp. - Pinheiro Juárez Coqueiro (El Colegio de México, A.C., 1980)
-